Targeted high mean arterial pressure aggravates cerebral hemodynamics after extracorporeal resuscitation in swine - Yael Levy; Alice Hutin; Fanny Lidouren; Nicolas Polge; Rocio Fernandez; Matthias Kohlhauer; Pierre-Louis Leger; Guillaume Debaty; Keith Lurie; Lionel Lamhaut; Bijan Ghaleh; Renaud Tissier (Critical Care, 2021)
Abstract Background Extracorporeal cardiopulmonary resuscitation (E-CPR) is used for the treatment of refractory cardiac arrest. However, the optimal target to reach for mean arterial pressure (MAP) remains to be determined. We hypothesized that MAP levels critically modify cerebral hemodynamics during E-CPR and tested two distinct targets (65–75 vs 80–90 mmHg) in a porcine model. Methods Pigs were submitted to 15 min of untreated ventricular fibrillation followed by 30 min of E-CPR. Defibrillations were then delivered until return of spontaneous circulation (ROSC). Extracorporeal circulation was initially set to an average flow of 40 ml/kg/min. The dose of epinephrine was set to reach a standard or a high MAP target level (65–75 vs 80–90 mmHg, respectively). Animals were followed during 120-min after ROSC. Results Six animals were included in both groups. During E-CPR, high MAP improved carotid blood flow as compared to standard MAP. After ROSC, this was conversely decreased in high versus standard MAP, while intra-cranial pressure was superior. The pressure reactivity index (PRx), which is the correlation coefficient between arterial blood pressure and intracranial pressure, also demonstrated inverted patterns of alteration according to MAP levels during E-CPR and after ROSC. In standard-MAP, PRx was transiently positive during E-CPR before returning to negative values after ROSC, demonstrating a reversible alteration of cerebral autoregulation during E-CPR. In high-MAP, PRx was negative during E-CPR but became sustainably positive after ROSC, demonstrating a prolonged alteration in cerebral autoregulation after ROSC. It was associated with a significant decrease in cerebral oxygen consumption in high- versus standard-MAP after ROSC. Conclusions During early E-CPR, MAP target above 80 mmHg is associated with higher carotid blood flow and improved cerebral autoregulation. This pattern is inverted after ROSC with a better hemodynamic status with standard versus high-MAP.